Transverse ion diffusion inside fixed charge narrow pores - Sulbaran, B.; Olivares-Rivas, W.; Colmenares, P.J. (Condensed Matter Physics, 2005)
The diffusion dynamics of ions inside a planar slit with a high constant surface
charge density was studied by solving the Smoluchowski/HypernnetedChain
equation for the mean first passage times. The behavior of local
properties, such as the potential of mean force, is correlated with the time
it takes for an ion to get adsorbed at the surface, and also with macroscopic
properties like the salt rejection coefficient and the apparent diffusion constant
in porous media, as a function of pore size. We show that the width of
the walls has an important effect on the transverse ion diffusion process. Дифузійна динаміка іонів всередині плоскої щілини з великою постійною густиною поверхневого заряду досліджувалась шляхом розв’язку супер-ланцюжкового рівняння Смолуховського для середніх часів перших переходів. Поведінка локальних властивостей, таких як
потенціал середньої сили, корелює з часом, необхідним для іону
бути адсорбованим на поверхні, а також з макроскопічними властивостями, такими як коефіцієнт несприйняття солі та константою
уявної дифузії в пористих середовищах як функція розміру пори.
Ми показуємо, що ширина стінок має суттєвий вплив на поперечний
іонний дифузійний процес.